Penatalaksanaan Fisioterapi pada Kasus Brachial Plexus Injury di RSUP Dr. Sardjito Yogyakarta: Case Report - Fauzi, Ahmad Fatih (Jurnal Fisioterapi Terapan Indonesia, 2025)
Brachial Plexus Injury (BPI) is one of the most severe peripheral nerve injuries, frequently resulting from traffic accidents and causing significant functional impairment of the upper limb. Management of BPI requires a multidisciplinary approach, including physiotherapy interventions aimed at restoring muscle strength, preventing atrophy, and improving sensory and motor function. This article reports the physiotherapy management of a 23-year-old male with BPI following a traffic accident, who underwent surgical procedures and rehabilitation at Dr. Sardjito Hospital, Yogyakarta. The method used is a case report with literature review conducted via PubMed using relevant keywords. Physiotherapy interventions included Neuromuscular Electrical Stimulation (NMES) and forced passive exercise. Evaluation results indicated improvements in muscle strength and prevention of muscle atrophy after three therapy sessions, although active motion limitations and sensory disturbances persisted. In conclusion, the combination of NMES and forced passive exercise is effective in increasing muscle strength and preventing atrophy in BPI patients, thereby supporting gradual and periodic functional recovery.